Perancangan dan Pembuatan Adapter Penghubung Keyboard IBM PS/2 dengan Port USB Personal Computer - Lim, Resmana; Christanto, Danny (Jurnal Teknik Elektro, 2004)
Universal Serial Bus (USB) as a new interface especially on Personal Computer (PC) has become a standard for interfacing many devices to PC such as printer, scanner, mouse, webcam, etc. In this paper, a device that can be recognized by USB host and communicate through USB port correctly was developed. It has been implemented by making an adapter therefore IBM PS/2 keyboard could be recognized and operated in a USB environment. The device used a PDIUSBD12 USB interface IC which handle USB protocol and an AT89C2051 microcontroller which handle all incoming or outgoing data from and to PDIUSBD12 or keyboard. The device has been tested and proven capable of handling enumeration process and transfer data from keyboard to PC via a USB port. Although the device didn't support all functions of the keys, but the main keys worked normally on pressing one key or even combination keys. Keywords : Universal Serial Bus, PS/2 Keyboard Adapter to USB port, PDIUSBD12. Abstract in Bahasa Indonesia : Universal Serial Bus (USB) sebagai suatu interface pada Personal Computer (PC) saat ini banyak digunakan untuk menghubungkan berbagai peralatan dengan PC seperti printer, scanner, mouse, webcam dan lain-lain. Dalam tulisan ini dibuat sebuah adapter untuk menghubungkan keyboard IBM PS/2 agar dapat dikenali dan dijalankan dalam lingkungan USB yang terdapat pada PC. Alat ini menggunakan sebuah IC interface USB yaitu PDIUSBD12 yang akan menangani protokol USB dan sebuah microcontroller yang akan menangani semua data yang keluar ataupun masuk dari dan ke PDIUSBD12 ataupun keyboard. Alat ini telah diuji dan terbukti mampu menangani proses enumerasi dan menyampaikan data yang diterima dari keyboard menuju PC via port USB. Meskipun alat ini tidak mendukung semua fungsi tombol pada keyboard, tetapi fungsi tombol-tombol utama bisa berjalan dengan normal pada penekanan satu tombol ataupun kombinasi beberapa tombol. Kata kunci : Universal Serial Bus, Adapter Keyboard PS/2 ke USB, PDIUSBD12.